If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + 7 = 3(2h + -1) Reorder the terms: 7 + 5h = 3(2h + -1) Reorder the terms: 7 + 5h = 3(-1 + 2h) 7 + 5h = (-1 * 3 + 2h * 3) 7 + 5h = (-3 + 6h) Solving 7 + 5h = -3 + 6h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-6h' to each side of the equation. 7 + 5h + -6h = -3 + 6h + -6h Combine like terms: 5h + -6h = -1h 7 + -1h = -3 + 6h + -6h Combine like terms: 6h + -6h = 0 7 + -1h = -3 + 0 7 + -1h = -3 Add '-7' to each side of the equation. 7 + -7 + -1h = -3 + -7 Combine like terms: 7 + -7 = 0 0 + -1h = -3 + -7 -1h = -3 + -7 Combine like terms: -3 + -7 = -10 -1h = -10 Divide each side by '-1'. h = 10 Simplifying h = 10
| X+7y=-20 | | k/2+1=k/3-1 | | x+35+35=180 | | -8=y-6 | | 8(n-3)-(2-n)= | | 5[h+2]=3[j-1] | | 3x(X+1)-3x= | | -9+w=-7 | | 4x+-9+-9y=6 | | -9=u+9 | | .5(100+A)=50 | | x(-53-15x)=0 | | 6+2(3e-1)= | | 29=-2(4x-5)+3(3x+6) | | 2-12x+6=0 | | 4x-7=2b+X | | 12p-7=8p+9 | | 16=2y-12 | | 11x-3=5x+5 | | 2g-3-3G-5=1 | | 40000*X=1550000 | | 51+7t=0 | | 9y=3+7x | | 34-4x=7-7x | | 3=5x-5 | | 17p+13q+p-5q-5p= | | 17p+13q+p+5q-5p= | | 16+5=7x | | 1=5x-5 | | 4w+17=93 | | -2=5x-5 | | 16a+16b+2c+2c-5b-4a= |